Association of Sphingosine‐1‐phosphate (S1P)/S1P Receptor‐1 Pathway with Cell Proliferation and Survival in Canine Hemangiosarcoma. (25th June 2015) - Rodriguez, A.M.; Graef, A.J.; LeVine, D.N.; Cohen, I.R.; Modiano, J.F.; Kim, J.‐H.
<x xml:space="preserve">Abstract</x> Background Sphingosine‐1‐phosphate (S1P) is a key biolipid signaling molecule that regulates cell growth and survival, but it has not been studied in tumors from dogs. Hypothesis/Objectives S1P/S1P1 signaling will contribute to the progression of hemangiosarcoma (HSA). Animals Thirteen spontaneous HSA tissues, 9 HSA cell lines, 8 nonmalignant tissues, including 6 splenic hematomas and 2 livers with vacuolar degeneration, and 1 endothelial cell line derived from a dog with splenic hematoma were used. Methods This was a retrospective case series and in vitro study. Samples were obtained as part of medically necessary diagnostic procedures. Microarray, qRT‐PCR, immunohistochemistry, and immunoblotting were performed to examine S1P1 expression. S1P concentrations were measured by high‐performance liquid chromatography/mass spectrometry. S1P signaling was evaluated by intracellular Ca2+ mobilization; proliferation and survival were evaluated using the MTS assay and Annexin V staining. Results Canine HSA cells expressed higher levels of S1P1 mRNA than nonmalignant endothelial cells. S1P1 protein was present in HSA tissues and cell lines. HSA cells appeared to produce low levels of S1P, but they selectively consumed S1P from the culture media. Exogenous S1P induced an increase in intracellular calcium as well as increased proliferation and viability of HSA cells. Prolonged treatment with FTY720, an inhibitor of S1P1, decreased S1P1 protein expression and induced apoptosis of HSA cells. Conclusions and clinical importance S1P/S1P1 signaling pathway functions to maintain HSA cell viability and proliferation. The data suggest that S1P1 or the S1P pathway in general could be targets for therapeutic intervention for dogs with HSA.